The role of T and B cells in human atherosclerosis and atherothrombosis - Ammirati, E (Clin Exp Immunol, 2015)
Far from being merely a passive cholesterol accumulation within the arterial wall, the development of atherosclerosis is currently known to imply both inflammation and immune effector mechanisms. Adaptive immunity has been implicated in the process of disease initiation and progression interwined with traditional cardiovascular risk factors. Although the body of knowledge regarding the correlation between atherosclerosis and immunity in humans is growing rapidly, a relevant proportion of it derives from studies carried out in animal models of cardiovascular disease (CVD). However, while the mouse is a well-suited model, the results obtained therein are not fully transferrable to the human setting due to intrinsic genomic and environmental differences. In the present review, we will discuss mainly human findings, obtained either by examination of post-mortem and surgical atherosclerotic material or through the analysis of the immunological profile of peripheral blood cells. In particular, we will discuss the findings supporting a pro-atherogenic role of T cell subsets, such as effector memory T cells or the potential protective function of regulatory T cells. Recent studies suggest that traditional T cell-driven B2 cell responses appear to be atherogenic, while innate B1 cells appear to exert a protective action through the secretion of naturally occurring antibodies. The insights into the immune pathogenesis of atherosclerosis can provide new targets in the quest for novel therapeutic targets to abate CVD morbidity and mortality.